Penyelundupan Bibit Lobster (Benur) Melalui Jalur Lintas Perairan Tanjung Jabung Barat Dalam Perspektif Kriminologis - Haryo Baskoro; Ferdricka Nggeboe; S Sahabuddin (Universitas Batanghari Jambi, 2026)
Poor lobster control or overfishing has led to a decline in the productivity of aquatic resources and renewable resources. Management that follows sustainability principles can increase the chances of breeding adults, maintain a minimum number of adults in each area, and improve habitats, thus boosting conservation and yields. However, in practice, this is hard to achieve because of the limited time to monitor the slow development and growth of lobsters, and it conflicts with regulations like licensing and law enforcement. The purpose of this research is to find out and analyze the factors causing the smuggling of lobster seeds (juvenile lobsters) through the waterways of Tanjung Jabung Barat. It aims to understand and identify the modus operandi of smuggling lobster seeds through these waterways. Additionally, it seeks to understand and analyze the obstacles in uncovering lobster seed smuggling in the Tanjung Jabung Barat waterways and the efforts to overcome them. The specification of this study is Analytical Descriptive research. In writing this thesis, the author uses the Empirical Juridical research type. The research approach employed is Socio-Legal Research. The factors causing the smuggling of lobster seeds through the Tanjung Jabung Barat waterway include basic needs like clothing and food, as well as economic needs. The modus operandi used by perpetrators to smuggle lobster seeds includes using private cars to transport them to company cargo ships or passenger ships. The obstacles in uncovering lobster seed smuggling through the Tanjung Jabung Barat waterway include (a) Internal factors and (b) External factors. The efforts to tackle lobster seed smuggling involve measures that are Pre-Emptive, Preventive, and Repressive. It is suggested that the Police should prioritize firm and repressive actions so that those who smuggle lobster seeds through waterways get a deterrent effect.